GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 232 species occurrences available in GBIF matching the query: TaxonKey: Eurya muricata Dunn. The dataset includes 232 records from 22 constituent datasets: 14 records from Naturalis Biodiversity Center (NL) - Botany. 4 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 10 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 1 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 2 records from CONN. 16 records from NMNH occurrence DwC-A. 1 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 4 records from Natural History Museum, Vienna - Herbarium W. 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 2 records from Harvard University Herbaria. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 89 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 2 records from Herbarium of Taiwan Forestry Research Institute. 3 records from Lund Botanical Museum (LD). 34 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 29 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 5 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 8 records from Royal Botanic Garden Edinburgh Herbarium (E). 2 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from SysTax - Botanical Gardens.
Keywords: GBIF; biodiversity; species occurrences